1996
DOI: 10.1364/josab.13.000148
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atomic density in high-order harmonic generation

Abstract: Influence of atomic density in high-order harmonic generationAltucci, C; Starczewski, Tomas; Mevel, E; Wahlström, Claes-Göran; Carre, B; Lhuillier, A Link to publication Citation for published version (APA): Altucci, C., Starczewski, T., Mevel, E., Wahlström, C-G., Carre, B., & L'Huillier, A. (1996). Influence of atomic density in high-order harmonic generation. Optical Society of America. Journal B: Optical Physics, 13(1), 148-156. DOI: 10.1364/JOSAB.13.000148General rights Copyright and moral rights for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 30 publications
6
61
0
Order By: Relevance
“…6 show optimal HHG efficiency at a few hundreds mbar for gas jets and a few tens mbar for Ne cells. These are typical values appearing in experiment [12,28]. To further verify our model, we simulate the cases studied experimentally in Ref [22].…”
Section: Phase-matching and Hhg Enhancementmentioning
confidence: 85%
See 2 more Smart Citations
“…6 show optimal HHG efficiency at a few hundreds mbar for gas jets and a few tens mbar for Ne cells. These are typical values appearing in experiment [12,28]. To further verify our model, we simulate the cases studied experimentally in Ref [22].…”
Section: Phase-matching and Hhg Enhancementmentioning
confidence: 85%
“…This approach especially improves the low HHG efficiency of helium [9]. For low atomic density, the efficiency is enhanced quadratically with pressure [12], but plasma defocusing starts to become important as the free electron density increases. A previous study has shown that plasma defocusing in neon at 80mbar can significantly reduce the peak intensity of an 800nm driver pulse and diverges the driver pulse energy within a few hundred microns [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lompré et al pointed out the importance of using a loose focusing geometry [11]. Altucci et al studied the influence of the pressure on the harmonic yield, showing the influence of defocusing due to free electrons at high pressure [12]. Recently, several groups have studied harmonic generation using ultra-short laser pulses focused into a hollow fibre [13][14][15], or forming a filament [16], reporting relatively high conversion efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with what was reported in [23] by Wang et al, and can be understood as due to the pressure dependence of phase matching and reabsorption of harmonics. A second effect can be identified in the spectra, a wavelength blue-shift (tuning) of all harmonic orders with increasing pressure [24]. In the figure we have used the center frequency (determined from a Gaussian least-square fit to each harmonic) of the harmonics at lowest pressure (2 mbar) as reference, and these are indicated as vertical dashed lines.…”
Section: Resultsmentioning
confidence: 99%